Antioxidant capacity and total phenolic content of hydrothermally-treated 'Fuerte' avocado - Daiuto, E. R. [UNESP]; Fumes, J. G F [UNESP]; Vieites, Rogério Lopes [UNESP]; Cabia, N. C. [UNESP]; Castro, R. S D [UNESP] (My University, 2011)
Avocados possess high nutritional value with proven effectiveness in preventing cardiovascular diseases, attributed primarily to their unsaturated fatty acids content. This fruit is also rich in carotenoids and vitamins, particularly vitamin E. This work evaluates the antioxidant capacity and total phenolic content of hydrothermally-treated Fuerte avocado. Fruits were selected and hydrothermally treated at 45°C for 5, 10, 15 and 20 min. They were then stored in a refrigerator (10 ± 10°C and 90±5% relative humidity) and evaluated over a 15-day period. The total phenolic content increased up to the sixth day of storage, and decreased thereafter, without differences between the treatments. The percentage of antioxidant capacity of the control and the hydrothermally-treated samples for 5 and 10 min increased during storage. Untreated fruits showed the highest percentage of antioxidant capacity. However, the antioxidant capacity of avocado fruits subjected to these treatments declined starting on the twelfth day of storage, possibly due to the fruits' senescence. Hydrothermal treatments for 15 and 20 min delayed fruit senescence while the antioxidant capacity continued to increase up to the fifteenth day of storage. No significant correlation was found between antioxidant capacity and total phenolic content. The antioxidant capacity of ripe Fuerte avocado was higher than that of unripe or overripe avocado.
Keywords: Antioxidant capacity; Bioactive compounds; Persea americana Mill.; Refrigeration; Persea americana